The development of prosodic focus marking in French - Destruel, Emilie; Lalande, Louise; Chen, Aoju (Frontiers in Psychology, 2024)
Focus (i.e., new or contrastive information in a sentence) can be realized via a range of linguistic means. French is traditionally described as a language favoring syntactic means, e.g., c’est cleft. Nevertheless, recent research shows that prosody is used to mark focus independent of syntactic cues. However, prosodic realization of focus in French-speaking children has rarely been examined, in contrast to increasing research on children acquiring languages that primarily use prosody for focus-marking. Against this background, we examined how French-speaking children use prosody to realize narrow focus and contrastive focus in the absence of syntactic means, compared to adults. A virtual robot-mediated picture-matching task was used to elicit SVO sentences from monolingual French-speaking adults (N=11), 5- to 6-year-olds (N=12), and 7- to 8-year-olds (N=15). These sentences were produced with narrow focus on either the subject or the object and contrastive focus on the object, as responses to wh-questions on the subject or the object and yes-no questions on the object. Linear mixed-effects logistic regression modeling on duration, mean intensity, mean pitch, and pitch range of the subject and object nouns showed that the 4- to 5-year-olds did not use any of these prosodic cues for focus marking but the 7- to 8-year-olds distinguished narrow focus from non-focus through an increase in duration, mean intensity and to a lesser degree, mean pitch in the object nouns, largely similar to the adults and tended to use mean pitch in the subject nouns, different from the adults. Our study thus corroborates the previous finding that French-speaking 4- to 5-year-olds do not use prosody for focus marking, different from their peers from languages replying more on prosody. Further, it provides new evidence that 7- to 8-year-olds use prosody to mark narrow focus on the object in a more adult-like manner than narrow focus on the subject, arguably caused by a more dominant role of syntactic means in the subject position in French.